PENGARUH FAKTOR INTERNAL TERHADAP KEMAHIRAN BERBAHASA INDONESIA PESERTA DIDIK PADA JENJANG SEKOLAH MENENGAH DI DKI JAKARTA (The Influence of Internal Factors towards Indonesian Language Proficiency of Students at the High School in DKI Jakarta) - Dwi Wahyuni; Denny Adrian Nurhuda; Harini Harini (Balai Bahasa Sulawesi Selatan, 2022)
Indonesian language proficiency is a person's ability to use Indonesian, both orally and in writing, as measured by a test instrument called Uji Kemahiran Berbahasa Indonesia (UKBI) Adaptif Merdeka. UKBI Adaptif Merdeka is a user-friendly application that has been tested en masse to 160,450 junior and senior high school students through Giat UKBI Adaptif Merdeka program in 2021. UKBI scores and predicates achieved by students indicate their level of proficiency in Indonesian. This study aims to examine the influence of internal factors on the scores and predicates of Indonesian language proficiency for junior and senior high school students who are participants in Giat UKBI Adaptif Merdeka in DKI Jakarta. The method used is quantitative method. The instruments used are UKBI Adaptif Merdeka and questionnaire about internal factors that affect language proficiency. The results showed that UKBI scores and predicates obtained by students varied. A total of 1.3% of participants obtained scores and predicates above the standard, 46.3% according to the standard, and the rest below the standard. The results also show that internal factors, namely interest, motivation, and talent have a simultaneous effect on the score/predicate of Indonesian language proficiency of students in DKI Jakarta.Keywords: Indonesian language proficiency, UKBI Adaptif Merdeka, Giat UKBI Adaptif Merdeka, internal factors